2004
DOI: 10.1111/j.1524-4725.2004.30375.x
|View full text |Cite
|
Sign up to set email alerts
|

Glove Perforation in Outpatient Dermatologic Surgery

Abstract: The risk of glove perforation in outpatient dermatologic surgery is lower than in many other medical specialties. The relatively high number of surgical procedures performed successively in outpatient dermatologic surgery, however, emphasizes the decisive relevance of an intact barrier between surgeon and patient. In view of the major fact that most perforations go unnoticed by the wearer, dermatologic surgeons must balance the improved safety of double gloving with costs and the loss of sensitivity and dexter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 21 publications
(40 reference statements)
0
11
0
1
Order By: Relevance
“…Many glove perforations go unnoticed by the operating physician. 15 Manual manipulations of suture needles with lacing and tying knots increase the risk of this unwanted occurrence. Accordingly, barbed sutures may reduce the incidence of glove perforations.…”
Section: Discussionmentioning
confidence: 99%
“…Many glove perforations go unnoticed by the operating physician. 15 Manual manipulations of suture needles with lacing and tying knots increase the risk of this unwanted occurrence. Accordingly, barbed sutures may reduce the incidence of glove perforations.…”
Section: Discussionmentioning
confidence: 99%
“…The preventive effect depends largely on the integrity of the glove. However, gloves may perforate unnoticed or may tear during use so hands can become contaminated [4,9,18-21]. Doebbeling et al [22] showed that 5 to 10% of hands of HCW’s were contaminated after glove removal.…”
Section: Discussionmentioning
confidence: 99%
“…and are found to be directly related to the experience of the surgeon, type of procedure being carried out,[9] and duration of the procedure. [10] Also, certain areas are more prone to being punctured than others. Using a double gloving technique to carry out high-risk surgical procedures involving wiring in patients who are infected with or carriers of blood borne disorders such as HIV reduces the risk of cross infection significantly.…”
Section: Discussionmentioning
confidence: 99%